Steps to Preventing Type 2 Diabetes: Exercise, Walk More, or Sit Less? - Tudor-Locke, Catrine; Schuna, John M. (Frontiers in Endocrinology, 2012)
Accumulated evidence supports the promotion of structured exercise for treating prediabetes and preventing Type 2 diabetes. Unfortunately, contemporary societal changes in lifestyle behaviors (occupational, domestic, transportation, and leisure time) have resulted in a notable widespread deficiency of non-exercise physical activity (e.g., ambulatory activity undertaken outside the context of purposeful exercise) that has been simultaneously exchanged for an excess in sedentary behaviors (e.g., desk work, labor saving devices, motor vehicle travel, and screen-based leisure time pursuits). It is possible that the known beneficial effects of more structured forms of exercise are attenuated or otherwise undermined against this backdrop of normalized and ubiquitous slothful living. Although public health guidelines have traditionally focused on promoting a detailed exercise prescription, it is evident that the more pressing need is to revise and expand the message to address this insidious and deleterious lifestyle shift. Specifically, we recommend that adults avoid averaging < 5,000 steps/day and strive to average ≥ 7,500 steps/day, of which ≥ 3,000 steps (representing at least 30 minutes) should be taken at a cadence ≥ 100 steps/min. They should also practice regularly breaking up extended bouts of sitting with ambulatory activity. Simply put, we must consider advocating a whole message to “walk more, sit less, and exercise.”